Dampak Penambahan Fly Ash Pada Campuran Beton Terhadap Kuat Tekan dan Durabilitas Beton Akibat Serangan Sulfat - Kushartomo, Widodo; Wildan, Vanessa Adistya; Prabowo, Andy (Department of Civil Engineering, Diponegoro University, 2025)
Concrete is the primary choice for construction projects, including its use in aggressive environments such as coastal areas. The high sulfate content in these environments poses a threat to the durability and compressive strength of concrete. The impact of sulfate attack on concrete can result in degradation and a decrease in concrete quality. Several methods have been used to maintain the durability of concrete, such as applying coatings to the surface of the concrete or using pozzolanic materials in the concrete mixture. In this study, Fly Ash was used as a pozzolanic material to reduce the impact of sulfate attack on concrete. The experiment involved adding Fly Ash to the concrete mixture in proportions of 0%, 10%, 20%, 30%, 40%, and 50% by weight of cement. Three test specimens were made for each variation in diameter and height of 10 cm and 20 cm, respectively. The durability test of the concrete used a magnesium sulfate (MgSO4) solution with a dry-wet cycle method according to SNI 3407-2008, which was conducted after curing in water for 28 days. The results of the test showed that adding Fly Ash to the concrete mixture has been proven to reduce damage and minimize the degradation of concrete quality due to sulfate attack compared to normal concrete without the use of Fly Ash. The use of Fly Ash also increased the compressive strength of all test specimens compared to normal concrete without Fly Ash.